Variations of the gift and the debt in Derrida, Mauss and Nietzsche: notes for a politics to come - Manrique , Patricia (Escritura e Imagen, 2023)
In the lines that follow, we are committed to thinking about the gift and its problematic relationship with debt, as well as justice and the event, in the formulation that Jacques Derrida carries out of them, proposing them as features of a gesture capable of signifying another politics, which Derrida tends to name as «democracy to come». To do this, the contrast with the gift will be established as proposed by Marcel Mauss in his famous essay and the Nietzschean concepts of gift and debt will be reviewed as interesting precedents of the Derridean approach.